Table of Content - - (Journal of Islamic Sciences, 2025)
Table of Content:1. The Sudanese Defensive Jihad Against the Rapid Support Forces (Rebels): A Comparative Jurisprudential Study with United Nations Law and the Universal Declaration of Human RightsAsst-Prof. Haith  Balla Abdlla Salim2. Treasure in the Light of the Holy QuranMs. Hasna Hamid Thamer3. Fundamentalist, jurisprudential, and intentional rules: types, differences between them, and their validity for deriving legal rulingsMr. Housin Mohammad Agah4. Marital Disobedience: An Islamic Social TreatmentDr. Musatafa Muhammad Karakira
Keywords: Journal of Islamic Sciences